2003
DOI: 10.1161/01.cir.0000084539.58092.de
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Statin Therapy Improves Cardiac Function and Symptoms in Patients With Idiopathic Dilated Cardiomyopathy

Abstract: Background— Chronic heart failure is associated with inflammation and neurohormonal imbalance. The 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase inhibitors, or statins, exert anti-inflammatory and vascular protective effects. We hypothesized that short-term statin therapy may have beneficial effects in patients with nonischemic heart failure. Methods and Results— Sixty-three patients with symptomatic, nonisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
292
2
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(321 citation statements)
references
References 40 publications
20
292
2
7
Order By: Relevance
“…5 -7 Moreover, statins were shown to improve cardiac function in patients with nonischemic dilated cardiomyopathy. 8,9 As in the present study, total cholesterol was significantly lower in the atorvastatin group and there was a trend towards significance for lower cholesterol in the other statin group. It cannot be entirely excluded that improved plasma lipid profile, at least partially, accounts for better outcomes.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…5 -7 Moreover, statins were shown to improve cardiac function in patients with nonischemic dilated cardiomyopathy. 8,9 As in the present study, total cholesterol was significantly lower in the atorvastatin group and there was a trend towards significance for lower cholesterol in the other statin group. It cannot be entirely excluded that improved plasma lipid profile, at least partially, accounts for better outcomes.…”
Section: Resultssupporting
confidence: 73%
“…Laufs et al randomized 14 patients with dilated cardiomyopathy to cerivastatin or placebo, and followed them for 20 wk. 8 Both standardized life quality and exercise capacity increased significantly in the statin group. Node et al examined the effect of simvastatin in 23 patients with nonischemic HF, and found improved EF and slightly (approx.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A statistically significant change was not observed in the placebo group. [26] Thus, by altering the regulation of nitric oxide and endothelin, statins may have a beneficial effect on endothelial function and systemic peripheral vascular resistance.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…10 Statins effectively improve cardiac function and increase the survival rate in patients with severe cardiac failure due to dilated cardiomyopathy without coronary arterial insufficiency. 13,14 In addition, statins upregulate and activate endothelial nitric oxide synthase (eNOS) and increase NO production through the PI3K-Akt-eNOS pathway. 15,16 Statins inhibit the formation of mevalonate and exhibit powerful anti-inflammatory effects, mediated by the inhibition of critical proteins such as Ras, Rho and NF-kB.…”
Section: Introductionmentioning
confidence: 99%